Porous Bilayer Electrode‐Guided Gas Diffusion for Enhanced CO2 Electrochemical Reduction - Yucheng Wang; Hanhui Lei; Hang Xiang; Yongqing Fu; Chenxi Xu; Yinzhu Jiang; Ben Bin Xu; Eileen Hao Yu; Chao Gao; Terence Xiaoteng Liu (Advanced Energy & Sustainability Research, 2021)
Comparing with the massive efforts in developing innovative catalyst materials system and technologies, structural design of cells has attracted less attention on the road toward high‐performance electrochemical CO2 reduction reaction (eCO2RR). Herein, a hybrid gas diffusion electrode‐based reaction cell is proposed using highly porous carbon paper (CP) and graphene aerogels (GAs), which is expected to offer directional diffusion of gas molecules onto the catalyst bed, to sustain a high performance in CO2 conversion. The above‐mentioned hypothesis is supported by the experimental and simulation results, which show that the CP + GA combined configuration increases the Faraday efficiency (FE) from ≈60% to over 94% toward carbon monoxide (CO) and formate production compared with a CP only cell with Cu2O as the catalyst. It also suppresses the undesirable side reaction–hydrogen evolution over 65 times than the conventional H‐type cell (H‐cell). By combining with advanced catalysts with high selectivity, a 100% FE of the cell with a high current density can be realized. The described strategy sheds an extra light on future development of eCO2RR with a structural design of cell‐enabled high CO2 conversion.